Tanggung Jawab Pidana Korporasi Rumah Sakit - Hasrul Buamona (Universitas Ahmad Dahlan, 2016)
Hospital is an institution that provides comprehensive health services on preventive, promotive, curative and rehabilitative to the public at largeas regulated in Article 1 (3) of Law Number 44 Year 2009 About the Hospital, which says